HEALTH AND MINING PRACTICES IN INDIGENOUS TERRITORIES - Will da Silva Pacheco; Dayanne de Nazaré dos Santos; Monique Teresa Amoras Nascimento; Deisiane da Silva Mesquita; Karytta Sousa Naka; Nádile Juliane Costa de Castro (Universidade Federal do Paraná, 2024)
Objective: To identify the repercussions of mining practices on Indigenous Territories on health. Method: A qualitative documentary study was conducted, based on online news articles from Brazilian and international newspapers published between March 2020 and December 2022. Data collection took place between December and January 2023. A content analysis was performed. Results: A total of 28 news articles from online newspapers were identified, revealing two core themes: Mining and Threats to Indigenous Peoples; and Exposure of Indigenous Peoples' Health. Conclusion: The expansion of illegal mining is evident, posing a threat to the isolation of indigenous peoples and weakening the control of health-related issues by epidemiological services. This research contributes to raising awareness about mining activities and indigenous health, enabling nurses to better understand emerging health issues and adapt their care practices.